Pengaruh Harga Emas Dunia, Indeks Dow Jones, Harga Minyak Dunia (Brent Crude Oil) Terhadap IHGS Perusahaan Pertambangan: Studi Empiris Perusahaan Sub Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2018 – 2023 - Sari, Amanda Amelia; Hidayat Nugroho, Rusdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The mining sector is one of the main commodity sectors in the modern economy. Over the last 5 years, investor interest in investing in the mining sector has increased rapidly. Movements in share prices of mining sector companies are influenced by several factors, including macroeconomics. This research aims to determine, test and analyze the influence of World Gold Prices, Dow Jones Index, World Oil Prices (Brent Crude Oil) on Mining Company IHSG (Empirical Study of Mining Sub-Sector Companies Listed on the Indonesian Stock Exchange for the 2018 - 2023 Period). The population in this research are all mining sector companies on the Indonesia Stock Exchange (BEI) for the period 2018 – 2023 with a total of 66 companies. Sampling used non-probability sampling with purposive sampling technique to obtain 37 companies. Secondary data was analyzed using multiple linear regression analysis techniques supported by SPSS 26 software. Hypothesis testing was carried out using the F test and T test. Based on the results of the F test (simultaneous), the results showed that World Gold Prices, Dow Jones Index, World Oil Prices (Brent Crude Oil ) has a significant effect on the share prices of mining sector companies on the Indonesia Stock Exchange (BEI).Research results prove that World Gold Prices, Dow Jones Index, World Oil Prices/Brent Crude Oil have a significant influence on stock prices The results of the T test (partial) show that World Gold Prices, World Oil Prices (Brent Crude Oil) have a positive and significant effect on share prices of mining sector companies, while the Dow Jones Index has no effect on share prices of mining sector companies. The variables World Gold Price, Dow Jones Index, World Oil Price/Brent Crude Oil have an influence of 71.3% on share prices of mining sector companies, while the remaining 28.7% is influenced by other variables not examined in this research model.